The Effects of Perceived Service Justice and Information Clarity on Outpatient Satisfaction in An Indonesian Public Hospital - Andi Mulyawan; Tasya Aspiranti; Dede R. Oktini (Kirana Publisher (KNPub), 2026)
Patient satisfaction is a key indicator of healthcare service quality and reflects patients' evaluation of the services they receive. Although Pasar Rebo Regional General Hospital (RSUD Pasar Rebo), Jakarta, has achieved a high level of public satisfaction, patient feedback continues to indicate concerns regarding service fairness and the clarity of information provided during outpatient care. This study aimed to examine the effects of perceived service justice and information clarity on outpatient satisfaction at RSUD Pasar Rebo, East Jakarta. A quantitative explanatory research design employing a survey method was used. Primary data were collected through questionnaires administered to 392 outpatient respondents and analyzed using descriptive statistics and multiple linear regression. Hypothesis testing was conducted using t-tests to examine the partial effects of each independent variable and an F-test to assess their simultaneous effect on patient satisfaction. The findings revealed that perceived service justice and information clarity had positive and statistically significant effects on outpatient satisfaction, both individually and simultaneously. Descriptive analysis indicated that respondents generally perceived service justice and information clarity to be at a good level. Nevertheless, several issues remained, particularly regarding queue management, administrative procedures, accessibility of information, and consistency in information delivery during peak service hours. Patient satisfaction was also categorized as good, although it remained at a moderate level, suggesting that patients generally had positive service experiences but that their expectations had not been fully met. The study concludes that strengthening fairness in service delivery and ensuring that information is clear, accessible, and consistently communicated are important strategies for improving outpatient satisfaction. These findings provide practical implications for hospital management in designing patient-centered service quality improvement initiatives.